Praslovanski ijevski samostalniki moškega spola v slovenskem knjižnem jeziku 16. stoletja - Čepar, Metod (Linguistica et philologica, 2017)
The main part of the monography ('Proto-Slavic Masculine i-Nouns in Slovenian Literary Language of the 16th Century') is the analyze of the reflexes of Proto-Slavic i-stem nouns of masculine gender in Slovenian literary language of the 16th century.The Proto-Slavic i-stem nouns of masculine gender in Slovenian literary language of the 16th century can reflect as nouns of o-stem masculine, i-stem feminine, i-stem masculine (gospod "sir", ljudje "people", partly also, pot "path"), u-stem (circumflected monosyllables), a-stem and in the plural mixed i-stem and o-stem (masculine) or mixed i-stem and o-stem (miš ˮmouseˮ) declension. Mostly the reflexes of i-stem declension are limited to individual case form and are not reflected in the overall paradigm. There is the increased conservation of i-stem declension in plural while in the singular the transition to o-stem patterns is larger.